Gestão de compras do programa nacional de alimentação escolar para o aumento da participação de agricultores familiares nas aquisições do Instituto Federal Goiano - Correia, Juliana Hernandez (2019)
The activities of Family Farming promote environmental, economic and social development, therefore, there is a need for its encouragement and maintenance by public policies. Among the policies, the Programa Nacional de Alimentação Escolar (PNAE) boosts work in the crop fields and promotes food security. Through Law n. 11.947/2009, at least 30% of the budget passed by the Fundo Nacional de Desenvolvimento da Educação (FNDE) for the purchase of food for school meals should be destined to the direct purchase of products from Family Agriculture. However, studies show that this percentage, in general, is not reached. In this perspective, this study intended to identify and propose improvements to the restrictions in the food acquisition process of school meals through the PNAE at the Instituto Federal Goiano in order to possibly promote the participation of a larger number of family farmers as suppliers. In order to do so, we applied questionnaires on a Likert scale to those involved in the process (family farmers and purchasing managers), which were explored using methodologies such as categorical analysis of data, variance and correlations. As a result, it has been identified that the main bottleneck in the process activities was Step 01 - Budget, at professional training points and knowledge about how the process is initiated. This step has a strong positive correlation with Step 10 - Receiving and payment term of the farmers, which implies that, when promoting the qualification of the servers, the evaluation of how the products are requested and stored and how the payment is given to the suppliers will be optimized. With this, a project was elaborated with changes in the activities of the purchasing process.